Role and impact of a specialized cardiometabolic clinic in managing high-risk patients with type 2 diabetes and atherosclerotic cardiovascular disease - Taher Modarressi (Elsevier, 2024)
Background: Lipid-related risk and residual cardiovascular risk remain high in patients with type 2 diabetes (T2D) and atherosclerotic cardiovascular disease (ASCVD). Significant treatment gaps exist in implementation of pluripotent and effective therapies that reduce these risks. Objective: This study evaluates the efficacy and impact of a dedicated, standalone cardiometabolic clinic designed to address treatment gaps through streamlined management and optimization of treatment strategies. Methods: We retrospectively collected data from the first 400 patients with T2D and ASCVD who underwent treatment at the clinic and presented for at least one follow-up visit. These patients were primarily managed for their cardiometabolic risks and received intensified lipid-lowering therapies, including adjunct non-statin therapies. Results: Significant findings included increased use of glucagon-like peptide-1 receptor agonists (GLP1RA) and sodium-glucose cotransporter 2 inhibitors (SGLT2i) to 84 % and 65 %, respectively, with 94 % of patients eventually on one therapy and 55 % on dual therapy. Increases in lipid-lowering therapies led to 89 % of patients achieving low-density lipoprotein cholesterol levels below patient-specific thresholds for intensification. Conclusion: This care model effectively manages high-risk patient needs, achieving significant intensification of lipid-lowering therapies and broad use of cardiometabolic drugs, and highlights the clinic's potential to serve as a model for similar high-risk populations.